A novel self-centering viscous damper for improving seismic resilience: Its development, experimentation, and system response. (15th March 2023) - Yan, Xin; Alam, M. Shahria; Shu, Ganping; Qin, Ying
Highlights: A novel disc spring-based self-centering viscous damper is presented. A series of performance tests of the proposed damper are conducted. The damper exhibits flag-shaped hysteretic responses with reliable performance. Theoretical expressions are developed and validated through test results. Performance comparison is conducted between different structural bracing systems. Abstract: A novel self-centering viscous damper (SCVD) is developed to improve the seismic resilience of structures. The proposed damper offers high flexibility in load resistance, deformability, and excellent velocity-dependent energy dissipation characteristics. The detailed configuration, recommended fabrication process, basic working principle, and restoring force model are presented first, followed by comprehensive experimental studies on the damper specimen, where different initial preload, loading frequency, and loading amplitude are considered. The specimen shows typical flag-shaped hysteretic behavior, little strength degradation, and reliable energy dissipation, where a maximum equivalent viscous damping of 38.33% is achieved at high frequency, and the self-centering mechanism can be fully realized at the end of loading. Moreover, a system-level analysis is carried out to evaluate the effectiveness of such self-centering dampers as bracing elements in a building to control seismic demands. Here, a buckling-restrained braced frame and a conventional self-centering braced frame are considered for comparison purposes. Nonlinear dynamic analyses indicate that the proposed system exhibits an improved control of the peak deformation, residual deformation, and peak floor acceleration.